Impact of Postoperative Weight Loss on Survival After Resection for Pancreatic Cancer. (31st January 2014) - Hashimoto, Daisuke; Chikamoto, Akira; Ohmuraya, Masaki; Abe, Shinya; Nakagawa, Shigeki; Beppu, Toru; Takamori, Hiroshi; Hirota, Masahiko; Baba, Hideo
Abstract : Background: The aim of this study was to assess the effects of postoperative body weight loss on long‐term survival after resection for pancreatic cancer. Methods : A total of 93 patients with primary pancreatic cancer underwent pancreatic resection between April 2005 and December 2011. Patient characteristics, preoperative body mass index, and changes in postoperative body weight were evaluated retrospectively and correlated with long‐term survival. Results : There was no significant association between survival and preoperative body mass index. Body weight fell by 8.4% at 2 months after surgery and by 9.0% at 4 months after surgery. Severe postoperative body weight losses, both at 2 months ( P = .033) and 4 months ( P = .014) after surgery, were significantly associated with poor prognosis, especially among patients with stage IA–IIA pancreatic cancer (n = 43) ( P = .005 at 2 months and P < .001 at 4 months). Additionally, severe body weight loss tended to be associated with shorter survival among patients with stage IIB–III pancreatic cancer (n = 50), although the difference was not significant. Multivariate analysis revealed that postoperative body weight loss was an independent prognostic factor. Conclusions : The results of this study demonstrated that pancreatic cancer patients with severe postoperative body weight loss have poorer postoperative outcomes.